The sense of life satisfaction of nursing students - Zalewska-Puchała, Joanna; Sowa, Agata; Majda, Majda; Bodys-Cupak, Iwona (Nursing in the 21st Century, 2015)
THE SENSE OF LIFE SATISFACTION OF NURSING STUDENTS Aim. The aim of this study was to determine the degree of life satisfaction of nursing students and its determinants. Material and Methodology. The study was performed by applying diagnostic survey, the questionnaire technique with the use of research tools in the form of: author’s questionnaire form, Subjective Happiness Scale by S. Lyubomirsky and H.S. Lepper, The Meaning in Life Questionnaire by M.F. Steger, P. Frazier, S. Oishii M. Kaler and Steen Happiness Index Questionnaire by M.P. Seligman, T.A. Steen, N. Park and C. Peterson. Statistical studies were carried out using the SPSS 17.0.0 software. The research comprised 90 full-time and part-time students at the faculty of nursing, Faculty of Health Sciences Collegium Medicum of Jagiellonian University. Results. Studies have shown that most of the students declared lack of time to spend with family and friends; almost half of the respondents have no time to develop their interests and participate in sports, they devote most of the time to study. Despite this, the same group of students received scores above the midpoint on the scale of happiness, the meaning of life questionnaire and happiness questionnaire. Statistical analysis showed that student`s life satisfaction is influenced by the financial situation, sport, assessment of themselves as a student, course of study, time spent on learning, assessment of past life. Conclusion. The majority of nursing students felt happines and satisfied with life.